Moisture, density, and consolidation properties of IODP Site C0023 from the Shallow Nankai Trough Subduction Zone, SW Japan - Junli Zhang (PANGAEA, 2020)
A total of 11 whole-round core samples from 450 to 1022 mbsf were recovered at Site C0023 during IODP Expedition 370. Moisture and density measurements and consolidation experiments were conducted in a shore-based laboratory. Moisture and density data include wet bulk density, grain density, porosity and water content, whereas consolidation experiments yield preconsolidation pressure, recompression index, compression index and expansion index.